2007
DOI: 10.1080/10826080701205760
|View full text |Cite
|
Sign up to set email alerts
|

Injection Drug Use, Multiple Hepatitis Virus Infections, and Migration: A German Study

Abstract: This article examines infection with viral hepatitis A, B, and C and socioethnic factors in a population of injection drug users seeking treatment. The study was conducted between 2001 and 2003 in a rural German hospital; selected sociodemographic and drug-related data as well as a serology for hepatitis A, B, and C were obtained from 1499 patients. Statistical analyses were performed by univariate analysis of variance and post hoc Scheffé tests or with the chi(2) test and Bonferroni adjustment. Ethnic minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Previous studies elsewhere showed that migrants without legal documentation might avoid seeking medical advice or entering treatment services because of fear of expulsion from the country [27,79]. Furthermore, some authors reported a more serious progression of opioid dependence in an immigrant population (leading to the acquisition of multiple infections) and interpreted this finding as part of a multifaceted acculturation problem [80]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies elsewhere showed that migrants without legal documentation might avoid seeking medical advice or entering treatment services because of fear of expulsion from the country [27,79]. Furthermore, some authors reported a more serious progression of opioid dependence in an immigrant population (leading to the acquisition of multiple infections) and interpreted this finding as part of a multifaceted acculturation problem [80]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, in Germany, minority patients had a more severe course of drug addiction in one study (Reimer et al, 2007), whereas in a study in Israel, former Soviet Union immigrants did not have more severe drug problems than native patients (Isralowitz, Reznik, Spear, Brecht, & Rawson, 2007). In Europe, knowledge about addiction of migrants is often limited due to lack of data, although some researchers examined this subject with attention [for example, see Grusser, Wolfling, Morsen, Albrecht, & Heinz (2005); Hjern (2004); Reimer et al (2007); Specka, Buchholz, Kuhlmann, Haasen, & Scherbaum (2010)]. In France, literature is scarce and the quantity of research appears inappropriate given the scale of the challenge.…”
Section: The Impact Of Migration On Explanatory Models and Addiction mentioning
confidence: 98%
“…These effects have been shown to relate directly to many health issues. For example, research has shown that immigrants to many countries report high levels of drug use that decline with acculturation (Grusser et al, 2005;Reimer et al, 2007;Prado et al, 2008); that foreign born children in the US tend to be healthier than children of the same age born in the US in linguistically isolated households (Lucas et al, 2005); that 40% of elderly Asians in new York City have clinical symptoms of depression (Rhee, 2009); that Asian women in the US aged over 65 years have a suicide rate more than double that of English-speaking women of the same age (Treas and Mazumdar, 2002); that the hepatitis B virus infection rate among linguistically isolated Asians in the US is 15-20% but only 0.4% for the population as a whole (Levy et al, 2005); that linguistically isolated women experience domestic violence at a rate of about 30-50% compared to about 16% for women in general (Pan et al, 2006); that children whose parents are linguistically isolated have high rates of developmental, academic, behavioral, and social problems that often persist into adulthood and may be passed from generation to generation (Yu et al, 2009); among many other similar effects. In Australia, high levels of acculturation stress among Sudanese migrants due to linguistic isolation have been observed (Milner and Khawaja, 2010).…”
Section: Language and Healthmentioning
confidence: 99%